Maintaining health professional education during war: A scoping review. Issue 8 (25th April 2022) - Dobiesz, Valerie A.; Schwid, Madeline; Dias, Roger D.; Aiwonodagbon, Benjamin; Tayeb, Baraa; Fricke, Adrienne; Pham, Phuong; Erickson, Timothy B.
Abstract: Purpose: War negatively impacts health professional education when health care is needed most. The aims of this scoping review are to describe the scope of barriers and targeted interventions to maintaining health professional education during war and summarise the research. Methods: We conducted a scoping review between 20 June 2018 and 2 August 2018. The search was restricted to English publications including peer‐reviewed publications without date ranges involving war and health professional education (medical school, residency training and nursing school), with interventions described to maintain educational activities. Two independent reviewers completed inclusion determinations and data abstraction. Thematic coding was performed using an inductive approach allowing dominant themes to emerge. The frequency of barrier and intervention themes and illustrative quotes were extracted. Articles were divided into modern/postmodern categories to permit temporal and historical analysis of thematic differences. Results: Screening identified 3271 articles, with 56 studies meeting inclusion criteria. Publication dates ranged from 1914–2018 with 17 unique wars involving 17 countries. The studies concerned medical students (61.4%), residents (28.6%) and nursing students (10%). Half involved the modern era and half the postmodern era. Thematic coding identified five categories of barriers and targeted interventions in maintaining health professions education during war: curriculum, personnel, wellness, resources, and oversight, with most involving curriculum and personnel. The distribution of themes among various health professional trainees was similar. The frequency and specifics changed temporally reflecting innovations in medical education and war, with increased focus on oversight and personnel during the modern era and greater emphasis on wellness, curriculum, and resources during the postmodern era. Conclusions: There are overarching categories of barriers and targeted interventions in maintaining health professional education during war which evolve over time. These may serve as a useful framework to strategically support future research and policy efforts. Abstract : This scoping review examined overarching barriers and interventions aimed at maintaining health professional education during war related to curriculum, personnel, wellness, resources, and oversight.